Case report: severe reversible cardiomyopathy associated with systemic inflammatory response syndrome in the setting of diabetic hyperosmolar hyperglycemic non-ketotic syndrome. Issue 1 (December 2015) - Berk, Justin; Wade, Raymond; Baser, Hatice; Lado, Joaquin
Abstract Background This case study features a woman who presented with clinical and laboratory findings consistent with hyperosmolar hyperglycemic non-ketotic syndrome (HHNS), systemic inflammatory response syndrome (SIRS), and non-thyroidal illness syndrome (NTIS) who was noted to have a transient decrease in myocardial function. To our knowledge, this is the first case discussing the overlapping pathophysiological mechanisms could increase susceptibility to SIRS-induced cardiomyopathy. It is imperative that this clinical question be investigated further as such a relationship may have significant clinical implications for prevention and future treatments, particularly in patients similar to the one presented in this clinical case. Case presentation A 53-year old Caucasian female presented to the Emergency Department for cough, nausea, vomiting and "feeling sick for 3 weeks." Labs were indicative of diabetic ketoacidosis. Initial electrocardiograms were suggestive of possible myocardial infarction and follow-up echocardiogram showed severely depressed left ventricular systolic function which resolved upon treatment of ketoacidosis. Conclusion We suggest that her cardiomyopathy could have three synergistic sources: SIRS, HHNS and NTIS. Overlapping mechanisms suggest uncontrolled diabetes mellitus and NTIS could increase susceptibility to SIRS-induced cardiomyopathy as seen in this case. HHNS and SIRS cause cardiac tissue injury through mechanisms including impairment of fatty acid oxidation and formation of reactive oxygen species, as well as modifying the function of membrane calcium channels. As a result, it is conceivable that diabetes may amplify the deleterious effects of inflammatory stressors on cardiac myocytes. This novel case report offers a path for future research into prevention and treatment of SIRS-induced cardiomyopathy in, but not exclusive to, the setting of diabetes.